Internet of Things Ultraviolet Sterilizer Receiver Box: How to Design and Construct? - Muhammad, Meizano Ardhi; Panuju, Achmad Yahya Teguh; Prayitno, Hadi; Pradipta, Rio Ariestia; Martinus, Martinus; Akbar, Gustian Ilham (International Journal of Electronics and Communications Systems, 2021)
COVID-19 is a virus that can spread through objects and depending on environmental conditions. It can last for several hours without destroying structures or disintegrating. Due to the COVID-19 pandemic, people were restricted from going outside to buy essential goods. Based on these conditions, it is necessary to design an IoT-based virus-safe package receipt box that is intuitive and comfortable for users to use, whether sending or receiving packages. People can control the system via remote control. Sterilization is carried out intelligently by considering the packet received. Design and construction of Internet of Things Ultraviolet Sterilizer Receiver Box use the Design Science Research Method. The methods consist of six stages: identify problem and motivate, define the objective of a solution, design and development, demonstration, evaluation, and communication. There are three parts of the system: sterilizer receiver box, mobile application, and Internet of Things. The system successfully passes the five testing scenarios: package received detection, package retrieved detection, ultraviolet irradiation, data service, and locking. The IoT-based virus-safe package receipt box can help maintain public health by preventing the COVID-19 virus with ultraviolet sterilization and supporting a modern lifestyle where people who work when the package arrives do not have to worry about the packages arriving.